A solar heat-pump system for air-conditioning, water heating and drying - Hawlader, Mohammad Nurul Alam; Jahangeer, K. A.; Shaochun, Ye; Choy, Tack Hoon (IIUM Press, 2011)
In this study, the performance of a three-in-one solar system is investigated. The three applications of the system are: air-conditioning, water heating and drying, which can be served simultaneously or independently. The presence of evaporator-collector enables the system to operate round the clock. Parallel arrangement of the evaporator and evaporator-collector is made to improve the system performance. A large fraction of the energy requirements is met by a combination of energy collected from sun, ambient and the energy recovered from a vapour compression heat-pump system, which also serves as an air-conditioner. The system shows good potential for implementation in commercial and residential applications and would give a new dimension in the process of replacement of conventional energy with renewable energy sources.